TREMOD: A microsimulation model for the Province of Trento (Italy) - Davide Azzolini; Martina Bazzoli; Silvia De Poli; Carlo Fiorio; Samuele Poy (University of Essex, Institute for Social and Economic Research (ISER), 2014)
This paper presents the main characteristics of TREMOD, a tax-benefit microsimulation model for the Italian province of Trento (Italy). TREMOD is based upon the EUROMOD platform microsimulation model, and its purpose is to inform local tax and welfare policies. TREMOD is a flexible tool that allows simulation of the effects of different types of public policies on a plurality of outcomes such as, for example, individuals' and households' income and well-being. The main strength of TREMOD is the high quality of the data used for its construction. The input database has been obtained by matching survey data (derived from a local representative survey on households' life conditions, Indagine sulle condizioni di vita delle famiglie trentine, ICFT) with administrative data on individual income tax returns. This aspect is one of the main strengths of TREMOD compared with other experiences in microsimulation modelling. As we show in this paper, the combination of survey and administrative data ensures good precision in the simulations and will allow for the integration of other administrative data sources including pension and labour market records. The first version of TREMOD is a 'static' microsimulation model.
Keywords: H24; I32; I38; 330; fiscal policies; microsimulation model; validation; administrative data; Trento